2022
DOI: 10.1002/cncr.34189
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA in head and neck cancer: Early successes and future promise

Abstract: The genetic components (DNA) of human papillomavirus-related throat cancer (in the oropharynx) might be measured after surgery to help to predict whether treatment has been successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In clinical setting, the use of ctHPVDNA during the diagnostic workup could improve accuracy, reduce costs and shorten diagnostic time 61 . In a prospective study, Siravegna et al 38 compared standard clinical approach versus imaging/physical exam findings associated to ctHPVDNA liquid biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical setting, the use of ctHPVDNA during the diagnostic workup could improve accuracy, reduce costs and shorten diagnostic time 61 . In a prospective study, Siravegna et al 38 compared standard clinical approach versus imaging/physical exam findings associated to ctHPVDNA liquid biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…35 In clinical setting, the use of ctHPVDNA during the diagnostic workup could improve accuracy, reduce costs and shorten diagnostic time. 61 In a prospective study, Siravegna et al 38 compared standard clinical approach versus imaging/physical exam findings associated to ctHPVDNA liquid biopsy. Although in limited number of patients (70 cases and 70 controls) the study showed that the diagnostic accuracy of this noninvasive approach was significantly better than standard of care (Youden index 0.937 vs. 0.707, P 1/4 0.0006), costs were 36%-38% lower, and the median diagnostic interval was 26 days shorter.…”
Section: Qualitative Assessmentmentioning
confidence: 99%
“…In the future, an alternative to post-treatment assessment for patients with HPV-DNApositive cancer may be measuring circulating tumour HPV-DNA (ctHPVDNA) [26][27][28]. Possibly combining FDG PET-CT and ctHPVDNA may be even more useful.…”
Section: Discussionmentioning
confidence: 99%